Hominin homelands of East Java: Revised stratigraphy and landscape reconstructions for Plio-Pleistocene Trinil. (15th May 2021) - Berghuis, H.W.K.; Veldkamp, A.; Adhityatama, Shinatria; Hilgen, Sander L.; Sutisna, Indra; Barianto, Didit Hadi; Pop, Eduard A.L.; Reimann, Tony; Yurnaldi, Dida; Ekowati, Dian Rahayu; Vonhof, Hubert B.; van Kolfschoten, Thijs; et al.
Abstract: Trinil (Java, Indonesia) yielded the type fossils of Homo erectus and the world's oldest hominin-made engraving. As such, the site is of iconic relevance for paleoanthropology. However, our understanding of its larger geological context is unsatisfactory. Previous sedimentological studies are around 100 years old and their interpretations sometimes contradictory. Moreover, the existing stratigraphic framework is based on regional correlations, which obscure differences in local depositional dynamics. Therefore, a new and more local framework is urgently needed. We carried out a comprehensive geological study of the Trinil area. Using a Digital Elevation Model, we identified seven fluvial terraces. Terrace deposits were described and OSL-dated and fluvial behaviour was reconstructed. The terraces were correlated with terraces of the Kendeng Hills (e.g. the hominin-bearing Ngandong terrace) and date back to the past ∼350 ka. Thus far, most of the Trinil terraces and their deposits had remained unidentified, confounding sedimentological and stratigraphic interpretations. The exposed pre-terrace series has a thickness of ∼230 m. Together with the terraces, it forms a ∼3 Ma record of tectonism, volcanism, climate change and sea-level fluctuations. We subdivided the series into five new and/or revised stratigraphic units, representing different depositional environments: Kalibeng Formation, Padas Malang Formation, Batu Gajah Formation, Trinil Formation and Solo Formation. Special attention was paid to erosional contacts and weathering profiles, forming hiatuses in the depositional series, and offering insight into paleoclimate and base-level change. The Trinil Formation provides a new landscape context of Homo erectus . Between ∼550 and 350 ka, the area was part of a lake basin (Ngawi Lake Basin), separated from the marine base level by a volcanic barrier, under dry, seasonal conditions and a regular supply of volcanic ash. An expanding and retreating lake provided favourable living conditions for hominin populations. After 350 ka, this role was taken over by the perennial Solo River. Landscape reconstructions suggest that the Solo formed by headward erosion and stream piracy, re-connecting the Ngawi Lake Basin to the plains in the west. Our study offers a local framework, but its Pleistocene landscape record has regional significance. Most of all, it forms a much-needed basis for future, detailed studies on the build-up of the hominin site of Trinil, its fossil assemblages and numerical ages. Highlights: The stratigraphy of Trinil forms a Plio-Pleistocene record of tectonism, volcanism, climate and sea-level changes. The Trinil riverbanks are partly made up of previously unnoticed fluvial terrace deposits. From 1.8 to 0.6 Ma the area was a coastal lowland at the foot of an andesitic volcano. From 550 to 350 ka the area was an isolated lake basin with ash-covered braidplains. The lake, and after 350 ka the Solo River, offered fortunate conditions for hominin occupation.